A dosimetric comparison of helical tomotherapy treatment delivery with real-time adaption and no motion correction - Hindmarsh, Jonathan; Crowe, Scott; Johnson, Julia; Sengupta, Chandrima; Walsh, Jemma; Dieterich, Sonja; Booth, Jeremy; Keall, Paul (Physics and imaging in radiation oncology, 2025)
[Display omitted] •Testing a helical tomotherapy system equipped with kV imaging and surface guidance.•A unified testing framework compared real-time adaption versus no motion correction.•Average reduction in 2 %/2 mm γ-fail rate was 17.3 % across 5 lung traces.•Average reduction in 2 %/2 mm γ-fail rate was 11.8 % across 3 prostate traces.•Helical tomotherapy system performed comparably to other real-time adaptive methods. This study assesses the ability of a helical tomotherapy system equipped with kV imaging and optical surface guidance to adapt to motion traces in real-time. To assess the delivery accuracy with motion, a unified testing framework was used. The average 2 %/2 mm γ-fail rates across all lung traces were 0.1 % for motion adapted and 17.4 % for no motion correction. Average 2 %/2 mm γ-fail rates across all prostate traces were 0.4 % for motion adapted and 12.2 % for no motion correction. Real-time motion adaption was shown to improve the accuracy of dose delivered to a moving phantom compared with no motion adaption. MeSH Keywords: Radiotherapy, image-guided; Radiation therapy, targeted.